2021
DOI: 10.21462/ijefl.v6i1.343
|View full text |Cite
|
Sign up to set email alerts
|

Brief ELT in Digital Classroom for Lazy Creative Lecturers (Option After Post Pandemic Recovery): Lecturers’ Perspectives

Abstract: This paper provides essential information for lecturers and educational institutions to think creatively in teaching English via online. The rapid development of Information and Communication Technology (ICT) and the Covid-19 emergency made lecturers and educational institutions think harder than usual. Higher education has used a powerful learning pattern and strategic policy to overcome the problem namely structure and unstructured online learning platform. The research aimed to find what platform is suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Finally, the EFL teachers from rural and urban areas claimed to need more workshop training on conducting online English language teaching and learning. It is in line with the study by Triana and Nugroho (2021) that found determining a model of learning model can be challenging, but a significant comprehension on it can result in a meaningful online teaching and learning. Moreover, The Indonesian government has held workshop training on online teaching.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, the EFL teachers from rural and urban areas claimed to need more workshop training on conducting online English language teaching and learning. It is in line with the study by Triana and Nugroho (2021) that found determining a model of learning model can be challenging, but a significant comprehension on it can result in a meaningful online teaching and learning. Moreover, The Indonesian government has held workshop training on online teaching.…”
Section: Discussionsupporting
confidence: 87%
“…The practical implication is given to teachers and policymakers to invest in IT and apply learning practices equal to increasing digital inclusivity [22];. Guideline administration [23]; Significantly affecting institutions' quality control [24]; Having significant implications in designing effective organizational policy to optimize faculty staff's research performance [25]; program evaluation [26]; Increasing Accounting System [27]. RQ2.…”
Section: Managementmentioning
confidence: 99%
“…And in the sphere of education, it caused "massive closure of educational institutions in more than 190 countries", leaving "in mid-May 2020 more than 1,200 million students of all levels of education" without face-to-face classes (Economic Commission for Latin America and the Caribbean (ECLAC)-UNESCO, 2020, p.1). Therefore, in this respect, universities had to opt for remote education (Sugianto & Ulfah, 2020;Triana & Nugroho, 2021) to prevent the spread of viruses and protect the integrity of the educational community personnel during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to adapt to this context and redesign the teaching 100% remotely is a challenge (Sugianto & Ulfah, 2020) that implies a "change of organizational character" (Ibáñez et al, 2018, p.2) to "combine their traditional procedures with their new non-face-to-face requirements" (García-Peñalvo, 2020, p. 1). In this sense, it is vital for teachers, students, and even parents and guardians to quickly acquire relevant competence and skills, such as knowledge related to digital teaching-learning that diminishes the negative impact on the students during this transition from face-to-face classes to online classes (Amiruddin & Jannah, 2021;König et al, 2020;Triana & Nugroho, 2021;.…”
Section: Introductionmentioning
confidence: 99%